The Influence of Competency and Self-Efficacy on Employee Performance Through Work Motivation in the Office of the Class I Mopah Merauke Airport Organizing Unit - Kayan Saputa; Meinarni Asnawi; Ernik Yuliana (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The research conducted at the Mopah Merauke Class 1 Airport Implementation Unit Office involved 106 individuals. Utilizing a total sampling technique, all 106 individuals were selected as respondents. The variables were measured using a Likert scale, and Structural Equation Modeling (SEM) was employed as the analytical method. Surprisingly, the analysis revealed that competence and self-efficacy did not exert a significant influence on employee performance. However, both competence and self-efficacy demonstrated a positive and noteworthy impact on work motivation. Furthermore, it was found that work motivation positively affected employee performance. Additionally, motivation was identified as a mediator in the relationship between competence and self-efficacy concerning the performance of Mopah Merauke Class 1 Airport Operator employees at the unit office. These findings shed light on the complex interplay between competence, self-efficacy, motivation, and performance within the context of airport operations, providing valuable insights for enhancing organizational effectiveness and employee productivity.